The Role of Celecoxib as a Potential Inhibitor in the Treatment of Inflammatory Diseases - A Review - Cruz, Josiane V.; Rosa, Joaquín María Campos; Kimani, Njogu Mark; Giuliatti, Silvana; dos Santos, Cleydson B. R. (Current Medicinal Chemistry, 2022)
This article aims at reviewing celecoxib as a potential inhibitor in the treatment of inflammatory diseases. The enzyme cyclooxygenase (COX) predominantly has two isoforms called cyclooxygenase 1 (COX-1) and cyclooxygenase 2 (COX-2). The former plays a constitutive role related to homeostatic effects in renal and platelets, while the latter is mainly responsible for the induction of inflammatory effects. Since COX-2 plays an important role in the pathogenesis of inflammatory diseases, it has been signaled as a target for the planning of anti-inflammatory intermediates. Many inhibitors developed and planned for COX-2 inhibition have presented side effects to humans, mainly in the gastrointestinal and/or cardiovascular tract. Therefore, it is necessary to design new potential COX-2 inhibitors, which are relatively safe and have no side effects. In this sense, celecoxib is the only potent, selective COX-2 inhibitor that is still commercially available (within the “coxib” family). Thus, celecoxib became a commercial prototype inhibitor for the development of anti-inflammatory agents for the COX-2 enzyme. This review provides inhibition highlights that should provide a structural basis for the design of promising new non-steroidal anti-inflammatory drugs (NSAIDs), which act as COX-2 inhibitors with lesser side effects on the human body.
Keywords: cyclooxygenase-2